Dynamic Access Control System Using Blockchain Technology and Provenance - Harika, Thippireddy; Pradeepini, Gera (Journal of Neonatal Surgery, 2025)
Blockchain technology has drawn a lot of interest because it can provide transparent, decentralized, and safe systems, which makes it a viable option for access control systems. Limitations with trust, scalability, and susceptibility to unwanted access are common with traditional centralized access control systems. Blockchain addresses these concerns providing secure, decentralized, and transparent systems, presenting a viable approach to access control systems. To get around the drawbacks of conventional systems, this research presents a revolutionary blockchain-based dynamic access control mechanism that takes provenance into account. The suggested architecture combines provenance with blockchain technology to produce a decentralized dynamic access control solution that can be tailored to different situations and access needs. The scheme allows dynamic updates to policies for access control, adjusting permissions based on changing conditions such as user roles, time, or context. This dynamic adaptability ensures that access privileges remain aligned with current needs, without requiring centralized intervention. It provides a robust, scalable approach for managing access control in environments where data integrity and accountability are critical Overall, by using a decentralized ledger to store access records, guaranteeing transparency and immutability, it provides a solid and scalable method for managing access control in settings where data integrity and accountability are crucial.